Standarisasi Biaya Produksi Kue Pada Usaha Kecil dan Menengah Di Kabupaten Bantul Yogyakarta - Hutauruk, Martinus Robert (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The Hapsari Jaya Small, and Medium Enterprise (SMEs) entity, located in Bantiul Regency, Yogyakarta, is growing rapidly in the home industry of various wet cakes. Hapsari Jaya has a superior product, the Macaroni Schotel cake, which dominates all types of damp cake production. As daily business operations continue, Hapsari Jaya still needs to have standardized production costs for its products, considering that it still uses a traditional management system, which has always been believed to be easier and faster. Hapsari Jaya experienced quite a lot of difficulty in standardizing the actual production costs for its wet cake products, so it also needed help in determining the cost of goods sold and a fair selling price to its customers and anticipating competition with competitors in the same business. This activity aims to assist in standardizing the production cost of Hapsari Jaya's superior wet cakes. The results of assistance in determining the cost of production in community service activities found a formula for standardizing production costs for Macroni Scouthel cake variants (raw material costs, direct labor, and factory overhead costs). So, it can be concluded that Hapsari Jaya has been able to determine the standardization of its production costs and the selling price level with the desired margin perception, making it easier to control its business in the future.